COMPARATIVE STUDY ON CHALKBOARD AND POWERPOINT TEACHING METHODS FOR EFFECTIVE LEARNING - SADDIKUTI PRASHANTHI,; T. LAKSHMI, (The Journal of Research ANGRAU, 2025)
This comparative study investigates the effectiveness of traditional chalkboard and modern  Power Point teaching methods in contemporary education. The study was conducted among third-year B.Sc. (Hons.) Agriculture students at Sri Venkateswara Agricultural College, Tirupati. A descriptive survey method was employed, utilizing questionnaires distributed via Google Forms, with 120 randomly selected responses analyzed using statistical tools. Results indicated that while PowerPoint presentations are perceived to offer better organization, clarity and visual aids, chalkboards are valued for their ability to stimulate interest, facilitate note-taking, and enhance student-teacher interaction. Specifically, 63.33 per cent of students found Power Point presentations well-organized and 86.67 per cent appreciated the visibility of lecture content. Conversely, 81.67 per cent of students reported better understanding through chalkboard teaching and 85.00 per cent valued the interaction it fosters. The study highlights that each method has distinct advantages: PowerPoint’s multimedia capabilities and ease of updating content versus the chalkboard’s simplicity and reliability. The findings suggest that an optimal teaching approach might integrate both methods to leverage their respective strengths, thereby enhancing educational quality and learning outcomes.